Children as inventors: orchestrating an informal pedagogic scenario with digital resources. (1st January 2014) - Crook, Charles; Harrison, Colin
A pedagogic scenario is described for providing primary school children with an understanding of the processes of invention while cultivating a sense of identity as 'inventor'. This scenario is positioned at the boundary of in-class and out-of-class experiences. Our central aim was to illustrate how digital resources might function to orchestrate the experience of invention. To this end, we distinguish the role of such resources in terms of their contributions to the following elements of invention: inspiration, expression, reflection and production. This framework for addressing invention as a creative activity allows it to be experienced as authentic, collaborative and free of biases associated with gender or curricular disciplines. Examples of the inventions conceived in this workshop are presented and a taxonomy for describing them is offered.